Relation between some summing operators - FERRADI Athmane (University Of Eloued جامعة الوادي, 2020)
The space of mid p summing operators was introduced by Karn and Sinha in[4] and was later developed by Botelho, Compos and Santos in 2017 in their article [3]. In this work we give a representation of the dual and bidual of the space p;mid of mid p-summing operators. We give a new factorization theorem for the well-known concept of strongly p-summing operators and we terminate with some relationships between these classes
Intervention
Keywords: p-summing operators; strongly p-summing operators; Cohen p-nuclear operators; factorization theorem